2010
DOI: 10.1128/ec.00309-09
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Reveals Novel Roles of the Ras and Cyclic AMP Signaling Pathways in Environmental Stress Response and Antifungal Drug Sensitivity in Cryptococcus neoformans

Abstract: The cyclic AMP (cAMP) pathway plays a central role in the growth, differentiation, and virulence of pathogenic fungi, including Cryptococcus neoformans. Three upstream signaling regulators of adenylyl cyclase (Cac1), Ras, Aca1, and Gpa1, have been demonstrated to control the cAMP pathway in C. neoformans, but their functional relationship remains elusive. We performed a genome-wide transcriptome analysis with a DNA microarray using the ras1⌬, gpa1⌬, cac1⌬, aca1⌬, and pka1⌬ pka2⌬ mutants. The aca1⌬, gpa1⌬, cac1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
115
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(126 citation statements)
references
References 84 publications
10
115
0
Order By: Relevance
“…Ras1-dependent stress control was mediated primarily by Cdc24-dependent signaling, as cdc24 mutants tightly phenocopied the stress response phenotypes exhibited by a ras1 mutant (353). Furthermore, a significant proportion of Ras/cAMP-dependent genes were also controlled by the environmental stress response (353).…”
Section: Major Morphogenetic Signaling Cascadesmentioning
confidence: 97%
See 4 more Smart Citations
“…Ras1-dependent stress control was mediated primarily by Cdc24-dependent signaling, as cdc24 mutants tightly phenocopied the stress response phenotypes exhibited by a ras1 mutant (353). Furthermore, a significant proportion of Ras/cAMP-dependent genes were also controlled by the environmental stress response (353).…”
Section: Major Morphogenetic Signaling Cascadesmentioning
confidence: 97%
“…Furthermore, in serotype A strains, the loss of the PKA regulatory subunit Pkr1 results in the overproduction of capsule, hypervirulence, and the suppression of phenotypes observed for a gpa1 mutant (160). Recently, it was shown that serotype A pka2 mutants are hypersensitive to osmotic shock under conditions of glucose starvation (353); hypersensitivity to osmotic shock is abolished by the additional disruption of PKA1, suggesting that Pka1 and Pka2 play opposite roles in the osmostress response (353). One of the key transcription factors that functions downstream of Pka1 in C. neoformans is Nrg1 (121).…”
Section: Major Morphogenetic Signaling Cascadesmentioning
confidence: 99%
See 3 more Smart Citations